2011
DOI: 10.1111/j.1479-8298.2010.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

First record of Leucothyreus albopilosus (Coleoptera: Scarabaeidae: Rutelinae: Geniatini) in lesions on stem of Eucalyptus citriodora and beehives of Apis mellifera

Abstract: Some species of the genus Leucothyreus MacLeay (Coleoptera: Scarabaeidae: Rutelinae: Geniatini) may cause damage to agricultural crops, principally due to action of adults that defoliate the plants. The aim of this study is to register the occurrence of the adults of Leucothyreus albopilosus Ohaus in lesions of plants of Eucalyptus citriodora Hook (Myrtaceae) and beehives of Africanized honeybees Apis mellifera Linnaeus (Hymenoptera: Apidae). In Mundo Novo, Mato Grosso do Sul, Brazil, on average 52 beetles per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…semipuinosus and L. ambrosius also remained safe in the soil inside chambers during dry and cold period of the year (Pereira et al, 2013;Gomes et al, 2014). Sexual dimorphism of L. albopilosus was also reported by Puker et al (2011) and dilated tarsomere were observed in male forelegs.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…semipuinosus and L. ambrosius also remained safe in the soil inside chambers during dry and cold period of the year (Pereira et al, 2013;Gomes et al, 2014). Sexual dimorphism of L. albopilosus was also reported by Puker et al (2011) and dilated tarsomere were observed in male forelegs.…”
Section: Discussionmentioning
confidence: 82%
“…This species showed a similar occurrence with other species Leucothyreus in this region. Puker et al (2011) recorded the occurrence of L. albopilosus in January, in the municipality of Mundo Novo, Mato Grosso do Sul. Adults of L. dorsalis were observed from September to December and from January to March (Rodrigues et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, Puker et al (2011) reported the occurrence of Leucothyreus albopilosus Ohaus, 1917 feeding on lesions on the stem of Eucalyptus citriodora Hook, 1848 in Mato Grosso do Sul. Puker et al (2009) also observed in Mato Grosso do Sul, larvae of Leucothyreus sp.…”
mentioning
confidence: 99%
“…Uma espécie não identifi cada de Melolonthidae foi observada causando danos em trigo no Mato Grosso do Sul (ÁVILA & PÍPOLO, 1992). Com relação às formas adultas registrou-se C. forsteri atacando a infl orescência de plantas de macaúba e Leucothyreus albopilosus Ohaus causando lesões em troncos de eucalipto (PUKER et al, 2011b).…”
Section: Culturas Atacadasunclassified